Characteristics of split-step skills of the world`s top athletes in badminton - Shishido, H.; Nishijima, T. (PLOS ONE, 2024)
Objective The purpose of this study was to quantitatively measure the split-step skills of the world`s top badminton players to clarify the characteristics underlying these skills when moving into the forehand position in the rear court.